Analysis of renewable energy integration options in urban energy systems with centralized energy parks. - Peniche Garcia, Ricardo (Cuvillier, 2017)
In der Arbeit werden mehrere Variationen zur zentralen Energieversorgung einer Metropolregion modelliert, simuliert und analysiert. Ziel dieser Variationen ist es, zum einen den Anteil Erneuerbarer Energien (EE) in der Strom- und Fernwärmeversorgung und zum anderen den Anteil des Stroms aus Kraft-Wärme-Kopplungsanlagen in der Stromversorgung zu erhöhen. Dabei wird auch eine Verringerung der jährlichen CO2-Emissionen sowie der jährlichen Gesamtkosten des Systems angestrebt. Insbesondere werden zwei Optionen für die Integration der EE analysiert: "Power to Heat"-Anlagen (PtH) und "Power to Gas to Combined Heat and Power"-Anlagen (PtGtCHP).

Several variations to the composition and operation strategy of a metropolitan region s centralized energy park are analyzed in this work. These variations are defined in an attempt to increase the system s share of renewable energy (RE) in electricity and district heating consumption, as well as the share of power from Combined Heat and Power (CHP) plants in electricity consumption. A decrease in the system s total annual CO2 emissions and total annual costs is also pursued. In particular, two RE integration options are analyzed: Power to Heat (PtH) units, and Power to Gas to Combined Heat and Power (PtGtCHP) plants.
Keywords: Energie; Energieversorgung; Kraft-Wärme-Kopplung; Energiewirtschaft; Stromversorgung; Wärmeversorgung; Fernwärme; Kohlendioxid; Emissionskontrolle; Minderung; Metropolregion; Erneuerbare Energie; Lebenszykluskosten; Bioenergie; Energiepark; Power-to-Gas; Emissionsminderung